Do Corporate Environmental Contributions Justify the Public Interest Defence? - Nigar Hashimzade; Gareth Donald Myles (Center for Economic Studies and ifo Institute (CESifo), 2017)
Corporations make significant direct contributions to environmental improvement and also indirect contributions, through expenditure on process and product innovation. We explore alternative motivations for these expenditures that look beyond the assertion that they are a consequence of business ethics. Two motives are explored: environmental improvement leading to reduced production costs, and publicized environmental expenditures boosting brand image. We analyze the equilibrium with environmental contributions and social welfare implications. These motives are then combined to determine whether environmental expenditures can justify public interest defence for the operation of a cartel. Using a variant of the Dixit-Stiglitz model we identify when reduced competition caused by a decrease in the number of active firms leads to greater environmental expenditures and higher welfare. However, allowing the operational firms to form a cartel and raise prices above Nash equilibrium levels always reduces environmental expenditures. Welfare falls, as a consequence, and the public interest defence fails.
Keywords: L49; Q58; 330; environment; public interest; cartel